Análise da revisão Cochrane : o uso de cigarros electrónicos para diminuição/cessação tabágica : Cochrane Database Syst Rev. 2014,12: CD010216 - Carneiro, António Vaz (2015)
Copyright © Ordem dos Médicos 2015